Microbial Contamination and Food Safety Aspects of Cassava Roasted Flour (“Rale”) in Mozambique - Andreia Massamby; Su-lin L. Leong; Bettina Müller; Lucas Tivana; Volkmar Passoth; Custódia Macuamule; Mats Sandgren (Microorganisms)
Cassava is an important staple food that contributes to the food security of small-scale Mozambican farmers. In southern Mozambique, cassava roots are usually processed into cassava roasted flour, locally known as “rale”. The handling and processing practices connected to “rale” production may introduce microbial contamination. We assessed the microbial contamination of “rale” processed in local farmers’ associations and consumed either locally or sold in rural markets. Microbial sampling was carried out both during the warmer rainy and cooler dry seasons, and microorganisms of relevance for food safety and fermentation were enumerated. The results revealed variation in terms of microbial diversity in all stages of cassava root processing. In samples collected in the warmer rainy season, molds, lactic acid bacteria, general aerobic bacteria and Bacillus spp. were isolated, whereas in samples collected in the cooler dry season, other groups of microorganisms such as yeasts and Staphylococcus aureus were present. Wickerhamomyces anomalus, Rhodotorula mucilaginosa, Pichia exigua, Meyerozyma caribbica and Torulaspora delbrueckii were the most frequent yeast species found within the cassava processing stages. Aflatoxin-producing molds were observed infrequently in this study, and only at low counts, thus, the risk for aflatoxin contamination appears to be low. The results obtained from the Illumina 16S rRNA gene sequencing can be considered a complementary technique to the plating methods relied on in this study. From a food quality and safety point of view, this staple food does not appear to pose a high risk for foodborne disease.